THE ROLE OF RELIGIOUS PRACTICES IN MAINTAINING THE MENTAL HEALTH OF GENERATION Z STUDENTS IN THE DIGITAL ERA - Serli Ariska; Fitriyah Fitriyah; Najwa Amalia; Surawan Surawan (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2026)
Anxiety disorders in Generation Z students have increased significantly due to academic pressure and the influence of social media, with Riskesdas 2023 data showing a high prevalence at the age of 15-24 years. This study aims to analyze the role of Islamic religious practices as a coping strategy in maintaining the mental health of Muslim students of Generation Z. The research uses a qualitative approach with a dual case study method on three students of UIN Palangka Raya through purposive sampling. Data were collected through semi-structured in-depth interviews, nonparticipant observations, and documentation, with validity guaranteed through triangulation and member examination. The results show that religious practices play an important role in bringing mental calm, reducing anxiety and overthinking, and strengthening resilience to academic stress. Prayer is the main coping mechanism, dhikr and Qur'an recitation function as a spiritual relaxation technique, strengthened by social support from families and campus communities. Religious practices are effective because they provide a framework of existential meaning that helps students reinterpret academic stressors in a broader spiritual perspective, while also activating physiological relaxation responses. These findings provide practical implications for the development of spiritualbased counseling programs and campus policies that integrate religious support in student mental health services.